Impact of Current Collectors on the Electrochemical Performance of Pseudocapacitive Material: Sr2FeCoO6 - Kumar P.; Verma H.; Mittal A.; Bhattacharya B.; Upadhyay S. (My University, 2025)
This work reports the synthesis of Sr2FeCoO6, double perovskite, via a wet chemical method. X-ray diffraction (XRD) analysis and Rietveld refinement confirmed the successful formation of pure, single-phase perovskite structure with the (Formula presented.) space group. The Raman spectrum showed minor peaks, suggesting structural distortions likely caused by defects. Transmission electron microscopy (TEM) revealed irregularly shaped polycrystalline particles, while Brunauer–Emmett–Teller (BET) analysis indicated an average surface area of 3.01 m2/g and a pore diameter of 37.8 nm. Current collectors, namely, carbon Toray paper, carbon cloth, nickel foam, and nickel strip, were selected to evaluate the electrochemical properties of Sr2FeCoO6. The morphology of the current collectors was captured using a scanning electron microscope (SEM). The electrochemical performance of bare and loaded (with Sr2FeCoO6) current collectors was assessed under similar measurement conditions. The high specific capacitance of the sample is observed over the carbon cloth and nickel foam to be 105.7 and 93.3 F/g, respectively, while bare carbon cloth shows very high capacitance. By comparing the performance of different current collectors, we have identified the key factors influencing the material's performance. This study will enhance our understanding of its potential applications in energy storage and other pertinent areas. © 2025 John Wiley & Sons Ltd.